2007
DOI: 10.1007/s11284-007-0411-y
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for particular seed‐borne fungi for seed germination and seedling growth of Xyris complanata, a pioneer monocot in topsoil‐lost tropical peatland in Central Kalimantan, Indonesia

Abstract: Hawaii yellow-eyed grass (Xyris complanata: Xyridaceae) inhabits infertile, acidic peat soil in the rainy tropical zone in Southeast Asia. This monocot plant produces a large number of dormant seeds in order to make a large deposit to seed bank in the soil. Under laboratory conditions, surface-sterilized X. complanata seeds are rarely able to germinate on sterilized peat moss bed; they require inoculation with either seed epiphytic or soil fungi to facilitate active seed germination. In the present study, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition, it has been found that Penicillium spp. promote seed germination, as well as seedling growth, and even protect seedlings of Picea glehnii (Yamaji et al 2001) and Xyris complanata (Tamura et al 2008). We now have evidence that Phoma sp., T. koningii and P. chrysogenum break mechanical but not physiological seed dormancy, and promote seed germination in O. streptacantha.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, it has been found that Penicillium spp. promote seed germination, as well as seedling growth, and even protect seedlings of Picea glehnii (Yamaji et al 2001) and Xyris complanata (Tamura et al 2008). We now have evidence that Phoma sp., T. koningii and P. chrysogenum break mechanical but not physiological seed dormancy, and promote seed germination in O. streptacantha.…”
Section: Discussionmentioning
confidence: 77%
“…promote seed germination, as well as seedling growth, and even protect seedlings of Picea glehnii (Yamaji et al. 2001) and Xyris complanata (Tamura et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from the disrupted mycelia using an Isoplant II DNA kit (Nippon Gene, Toyama, Japan). Using the resulting DNA as the template, the ITS region was amplified by PCR using a pair of universal primers (forward ITS 1, 5=-TCCGTAGGTGAACCTGCGG-3=; and reverse ITS 4, 5=-TCCTCCGCTTATTGATATGC-3=) as reported before (22). The PCR amplicon (600 bp) was sequenced using a BigDye Terminator v 3.1 cycle sequencing kit (Applied Biosystems, Tokyo, Japan) with primer ITS 4 according to the protocol recommended for an ABI Prism 310 genetic analyzer (Applied Biosystems, CA).…”
Section: Methodsmentioning
confidence: 99%
“…With those isolates that had sporulated, inoculum was prepared by adding 10 ml sterile distilled water to a colony, scraping conidia from the agar surface with a sterile scalpel, and adjusting the concentration to approximately 5 × 10 6 conidia/ml with a hemocytometer. For fungal isolates that failed to sporulate, mycelial suspensions were prepared as follows (Tamura et al, 2008). Fungal isolates were cultured with shaking in 50-ml potato dextrose broth medium at 22°C for several days, and the resulting mycelium was homogenized with a blender (Nippon Seiki, Nagaoka, Japan) after removal of the culture medium.…”
Section: Pathogenicity Testsmentioning
confidence: 99%